Profiles of Beef Cattle Breeding Based on Local Resources in Sumenep Regency (A case study at KTT Sumber Hasil Talang Village, Serongi District, Sumenep Regency, East Java) - J. Efendy (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2016)
Madura cattle breeding has long had a strategic role in supporting local economy. This study aimed to identify the profiles of beef cattle breeding based on local resources. Location of the studywas in Sumber Hasil farmer group, Talang Village, Seronggi Sub district, District of Sumenep Madura, East Java. The data collected were primary and secondary data and analyzed descriptively. Beef cattle breeding has been practiced using Madura cattle sincethe 1980’s. Rearing system was intensive, in which the livestock were kept in the pen all the time with cut and carry feeding system. The feed offered consisted of elephant grass, field grass, seam grass, bamboo leaves, complete feed, and others. In addition, 3 kg of rice bran per head was provided on daily basis. Most of the cattle was kept in the pen/cages that belonged to the farmer, and the rest was kept in the communal cage belonged to the farmer group. Breeding system was mostly (97%) with natural mating and the rest with artificial insemination (AI). Service per conseption for the former was mostly one times (92.39%).Calving interval and anestrus post partus of madura cows during the time between 2012 and 2014 was 13.49±3.10 months and 55.38±18.39 days, respectively.